2021
DOI: 10.3390/ijms22094883
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Control of Collagen-Dependent Platelet Responses by Thrombospondin-1—Comparative Analysis of Platelets from Neonates, Children, Adolescents, and Adults

Abstract: Platelet function is developmentally regulated. Healthy neonates do not spontaneously bleed, but their platelets are hypo-reactive to several agonists. The mechanisms underlying immature platelet function in neonates are incompletely understood. This critical issue remains challenging for the establishment of age-specific reference ranges. In this study, we evaluated platelet reactivity of five pediatric age categories, ranging from healthy full-term neonates up to adolescents (11–18 years) in comparison to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…The neonatal platelet hyporeactivity is likely an integral part of this balanced system, but the specific cellular interactions and pathways involved need to be elucidated. Furthermore, while some studies have shown significant improvement in platelet reactivity in newborn infants by 10 to 14 days of life, 49,65 more recent studies assessing platelet activation in different age groups (from neonates to adolescents) have found that age‐dependent improvements in platelet reactivity follow highly variable patterns, depending on the platelet agonist and the platelet activation marker studied 66,67 . Interestingly, some studies have identified platelet functional deficiencies extending into adolescence 66,67 .…”
Section: Future Research Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The neonatal platelet hyporeactivity is likely an integral part of this balanced system, but the specific cellular interactions and pathways involved need to be elucidated. Furthermore, while some studies have shown significant improvement in platelet reactivity in newborn infants by 10 to 14 days of life, 49,65 more recent studies assessing platelet activation in different age groups (from neonates to adolescents) have found that age‐dependent improvements in platelet reactivity follow highly variable patterns, depending on the platelet agonist and the platelet activation marker studied 66,67 . Interestingly, some studies have identified platelet functional deficiencies extending into adolescence 66,67 .…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Furthermore, while some studies have shown significant improvement in platelet reactivity in newborn infants by 10 to 14 days of life, 49 , 65 more recent studies assessing platelet activation in different age groups (from neonates to adolescents) have found that age‐dependent improvements in platelet reactivity follow highly variable patterns, depending on the platelet agonist and the platelet activation marker studied. 66 , 67 Interestingly, some studies have identified platelet functional deficiencies extending into adolescence. 66 , 67 The mechanisms regulating the neonatal platelet hyporeactivity and the complex transition from a neonatal to an adult platelet are poorly understood, and should be the focus of future research.…”
Section: Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy individuals, coagulation is tightly regulated to maintain the hemostatic balance between bleeding and thrombosis. The developing hemostatic system matures in several phases from fetus to adult, gradually changing and adapting to the requirements of each developmental stage [ 1 , 2 , 3 ]. Consequently, neonatal hemostasis differs from that of adults and has several peculiarities [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of the functional structure of neonatal platelets showed lower surface expression of GPIbα (CD42b) and varying expression of P-selectin and integrin αIIbβ3 depending on gestational age [ 19 , 20 , 21 , 22 ]. Neonatal platelets exhibit reduced granule secretion upon stimulation, resulting in less shedding of bioactive molecules into circulation [ 3 , 14 ]. We showed that inorganic polyphosphate (PolyP), a prothrombotic substance accumulated in platelet dense granules, is shed to a lesser extent by neonatal platelets than adult platelets.…”
Section: Introductionmentioning
confidence: 99%